2020
DOI: 10.31838/jcr.07.02.109
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Relationship Between Psychological Capital Andjob Attitudes With the Mediating Effect of Work Engagement in Hotel Industry

Abstract: Meeting the challenges of effective human resources management needs new thoughts and approaches. In order to expand the traditional perspective of economic capital, human capital and social capital have been paid more and more attention. This paper proposes that psychological capital can affect employees' attitudes from two aspects, namely, organizational commitment and job satisfaction. Based on the perspective of individual psychology, this article provides reviews of literature on this topic and explains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Luthans and Youssef-Morgan (2017) have rearranged these four dimensions as an acronym (HERO), representing hope, efficacy, resilience and optimism. Several researchers found that PsyCap has positive outcomes such as job satisfaction and commitment (Kong et al , 2018; Zhen and Mansor, 2020).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Luthans and Youssef-Morgan (2017) have rearranged these four dimensions as an acronym (HERO), representing hope, efficacy, resilience and optimism. Several researchers found that PsyCap has positive outcomes such as job satisfaction and commitment (Kong et al , 2018; Zhen and Mansor, 2020).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Systematic actions may therefore continue to have a favorable impact on job attitudes (Ngo et al. , 2013; Sahoo et al ., 2015; Jung and Yoon, 2015; Zhen and Mansor, 2020; Ali et al ., 2022). Psychological capital therapies have been discussed in some earlier studies (Luthans et al ., 2006; Rew et al ., 2014), and this could serve as a good place to start.…”
Section: Theoretical Implicationmentioning
confidence: 99%
“…KKT'ye göre, çalışanlar her zaman ciddiye aldıkları kaynakları elde etmeye, korumaya ve sürdürülebilir kılmaya odaklanmaktadır. Çalışanlar, gerilim ve stresle başa çıkmak için kaynaklara ihtiyaç duymakta ve daha çok kaynağa sahip olmaya çalışmaktadırlar (Hobfoll, Halbeslen, Neveu ve Westman, 2018;Zhen ve Mansor, 2020). KKT kapsamında bu kaynaklardan biri de psikolojik sermaye olarak değerlendirilebilir (Bogler ve Somech, 2019;Chiesa, Fazi, Guglielmi ve Mariani, 2018).…”
Section: Introductionunclassified